Teori gelombang spin dan kemagnetan di subpermukaan ferromagnet dengan pengurangan tukar ganti permukaan - Ahmad, Shamsuddin; Kamis, Ismail; Md. Raji, Abdul Wahid (1992)
Green's function for the subsurface of semi-infinite ferromagnet is derived by using "adlayer method". This Green's function is used to calculate subsurface density of states and temperature dependence of subsurface magnetization M (T) of spin wave. At temperatures as low as 1% of the Curie temperature T, neither softening surface exchanges nor position of subsurface atomic layers has any effect on the initial T law for subsurface magnetization M (T). The subsurface magnetization M (T) above these temperatures obeys a T law whose prefactor is determined by surface exchanges and the position of subsurfaces.